Karl Adam Catholicism in German culture - Krieg, Robert A. 1946- (Univ. of Notre Dame Press, 1992)
Here Robert Anthony Krieg, C.S.C., unites biography and theology in an insightful analysis of Adam's most influential works, showing how he crafted a theology for his time, one that embodied the central tenets of Christian belief while simultaneously adopting the language of German neoromanticism
Keywords: Adam, Karl; Adam, Karl <1876-1966>; Adam, Karl -- 1876-1966; Biografie